Residual Stresses Characterisation of Hard Ceramic Coating (SiC-5wt%Al2O3) Using X-Ray Diffraction Technique - Samah R. Hassan; Mudhar. A. Al-Obaidi; Hamid M. Mahan; Konovalov Sergey (Journal of Techniques)
The aim of this study is to measure residual stresses, specifically in wear protection coating, using the sin2ψ based on the X-ray diffraction technique. The combination of silicon carbide substrate and aluminium oxide (SiC-5wt.% Al2O3) is used as the wear protection coating, and AlNi alloy represents the bond coat, which is formed by the flame spraying method on the mild steel substrate. This in turn has enabled to reduce the thermal expansion constant between the substrate and composite ceramic layer. The diffraction angle, 2θ, is measured experimentally, and the lattice spacing is calculated using Bragg's Law using the measured diffraction angle and the known X-ray wavelength. Interestingly, stress calculations for the samples demonstrate a linear relationship of a slop proportionate to stress same as to homogenous isotropic samples in a bi-axial stress. Thus, the relationship between dspacing and sin2ψ is demonstrated as a straight line with a slope proportional to stress. However, the oscillatory trend showed the existence of in-homogeneous stress distribution. To resolve this challenge, X-ray elastic parameters are deployed instead of Poisson ratio (ν) and Young's modulus (E) values. The value of the residual stresses for these coatings calculated is compressive residual stresses of (-594.029 MPa).